Using The Jakarta Post (Daily News) To Improve Academic English Vocabulary of The United English Forum (UEF) Members In Makassar - Munawwarah Munawarah; Ramli Ramli; Sudirman Sudirman (Jounal of Primary Education, 2020)
The objective of this research is to discover whether using The Jakarta Post newspaper could improve the academic vocabulary of UEF members in Makassar or not. The population was 100 with 40 samples. Samples were determined using random sampling technique. I used quasi experiment design where 20 members were in the control class and 20 were in the experimental class. Members of UEF Makassar in control class did not receive a treatment while those in experimental class were treated up to three meetings and given an extra article to study at home. The tests consist of 20 questions from rearranging words to translating sentences. The result shows that using English newspaper from The Jakarta Post can improve academic vocabulary of UEF members in Makassar. It can be seen from the average test scores of students before and after given treatments. The improvement was quite significant from 47.75 to 81. It was proven by the result of the statistical analysis of the significant level, p= 5% dan p= 1%, with degree of freedom (df) = 38 indicating that the t-test value of the students’ academic vocabulary (3,246) was higher than t-table value (2,02 and 2,71) or 2,02 < 3,246 > 2,71.